Agreement on sanitary and phytosanitary measures : computer based training (WTO GenevaCH)
Presents an interactive guide to the agreement. Guides users through the agreement in a simple ste-by-step manner. Includes text, video and audio material complemented by a multiple choice test to enable users to monitor their individual progress. Includes the text of the Agreement.
Keywords: TRADE AGREEMENTS